PERSPEKTIF MAQASHID AL-SYARIAH DALAM PENYELENGGARAAN JAMINAN PRODUK HALAL DI INDONESIA PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL - Muhammad Aziz (Al Hikmah: Jurnal Studi Keislaman, 2017)
This study will reveal how the review of maqashid al-syariah in the implementation of Halal Product Guarantee after the enactment of Law No. 33 of 2014 on Halal Product Guarantee in Indonesia? Before the enactment of Law No. 33 of 2014 on Halal Product Guarantee, the implementation and implementation of Halal Product Guarantee is managed by LPPOM MUI. There are many problems when the implementation of halal product guarantee is still managed by private institutions. Therefore, the government finally issued Law No. 33 of 2014 on Halal Product Guarantee. The two objectives contained in Law No. 33 of 2014 on the guarantee of halal products, are important components that must be realized in human life, so that human life will be regarded as an optimal life. The sense of comfort, safety, safety and certainty of halal products circulating around Indonesia is important (dharuri) in the life of Muslims in Indonesia, so it must be realized, one of them only through the enactment of Law No. 33 of 2014 on the guarantee of halal products. From the analysis that has been conducted this study concludes that the implementation of the guarantee of halal products after the issuance of Law No. 33 of 2014 on the guarantee of halal products is the responsibility of the institution called the Halal Product Security Management Agency (BPJPH), which is under the auspices of the Ministry of Religious Affairs . In the perspective of maqashid al-shariah, first, UU JPH can provide comfort, safety, safety, and certainty of Halal Product availability for public purpose of guarantee implementation to improve halal product. Second, UU JPH can add value for business actors to produce and sell Halal Products.